Evaluating the role of operating temperature and residence time in the torrefaction of betel nutshells for solid fuel production - Kitrungloadjanaporn, Pongpathai; Sang, Le Quang; Pukdum, Jirasak; Phengpom, Tinnapob (International Journal of Renewable Energy Development, 2023)
This research addresses the urgent need for sustainable bioenergy alternatives, specifically evaluating betel nutshells as potential replacements for conventional biomass materials like coconut and palm fibers. The objective of the study was to gauge the inherent bioenergy potential of betel nutshells through an investigation of torrefaction under varying conditions, specifically temperatures ranging from 200-300 °C and residence times between 20-60 minutes in an inert environment. In this study, proximate analyses were utilized to investigate essential characteristics including moisture content, volatile matter, ash content, and fixed carbon, while a bomb calorimeter was used to determine their higher heating values. Initial results indicated that untreated betel nutshells had higher heating values and compositional similarities to coconut and palm fibers, highlighting their potential as a bioenergy source. Advanced torrefaction processes, involving increased temperatures and extended residence times, raised the fixed carbon content and reduced moisture in betel nutshells, thereby optimizing their higher heating value. This improvement is attributed to the decomposition of covalent bonds in the biomass structures, leading to the release of volatile compounds and consequent reductions in both oxygen-to-carbon and hydrogen-to-carbon ratios. Remarkably, at an operating temperature of 300 °C and a residence time of 60 minutes, torrefied betel nutshells reached a higher heating value of 25.20 MJ/kg, marking a substantial 31.39 % increase compared to untreated specimens. This study conclusively positions betel nutshells, typically considered agricultural waste, as competitive alternatives to traditional biomass resources in the biofuel industry.